Wandering gallbladder wrapping hepatoduodenal ligament and mimicking gastrointestinal stromal tumor at imaging. Case report and literature review - Malerba, Silvia; Puglisi, Giuliana; Panzera, Piercarmine; Pasculli, Alessandro; Prete, Francesco Paolo; Gurrado, Angela; Testini, Mario (Italian Journal of Anatomy and Embryology, 2023)
Wandering or free-floating gallbladder is a rare anomaly of position of the gallbladder, characterized by an unusually long or absent mesentery. This condition may present clinically as an emergency case of gallbladder torsion or as part of a complex clinical picture, where patients may present symptoms that trace to gallbladder pathology, but show morphologic features that are distant from gallbladder disease. We present a case where a wandering gallbladder wrapping around the hepatoduodenal ligament adhered to the stomach mimicking features of a gastrointestinal stromal tumor at preoperative imaging.